Assessment of Innovative Approaches to Flood Risk Management and Financing in Agriculture : The Thailand Case Study - World Bank (Washington, DC, 2013)
The World Bank recently conducted research and concept-testing activities to investigate the expansion of the index approach from drought to flood. The main objective was to assess prerequisite conditions, as well as practical and efficient methods, to conceptualize and potentially implement index-based insurance for agricultural flood losses. In addition, the work assessed how modern technologies such as flood modeling and remote sensing-which are widely used to support flood risk mapping, and flood detection, warning and control-could be harnessed to support the design of such flood insurance programs for rural clients. This paper summarizes the findings from work carried out from September 2005 to April 2008 in the Muang Petchaboon District of the Petchaboon province in Thailand. The next section illustrates the importance of flood risk in agriculture and challenges in providing flood insurance. The following section describes the flood index insurance concept and methodology that were tested during the feasibility study. Section four highlights the findings from the Petchaboon province of Thailand, and the final section synthesizes lessons learned and recommends areas for future research and applications. Finally, it is important to recognize that the process of quantifying weather risk, and of creating an operational system which combines risk and asset information, have much broader applications than simply for index-based weather insurance or other risk transfer solutions.